2020
DOI: 10.33545/gynae.2020.v4.i3d.599
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between Total Laparoscopic Hysterectomy (TLH) and conventional Total Abdominal Hysterectomy (TAH) in non-neoplastic uterine diseases

Abstract: Introduction: In the past decade, laparoscopic route of surgery has been on an increase especially for nonneoplastic uterine diseases. The present study aims to study and compare between Total Laparoscopic Hysterectomy (TLH) and conventional TAH (Total Abdominal Hysterectomy) in terms of characteristics like blood loss, operative time, intraoperative complications, postoperative pain & mobilisation, analgesic requirements, duration of hospital stay and finally patient satisfaction. Materials and methods: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
1
5
1
Order By: Relevance
“…A large uterus can be removed through the vagina, and hand morcellation is sometimes required. The average uterine size was reported to be smaller in TLH than in TAH;[ 1 3 5 ] however, this was not significant in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…A large uterus can be removed through the vagina, and hand morcellation is sometimes required. The average uterine size was reported to be smaller in TLH than in TAH;[ 1 3 5 ] however, this was not significant in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Intraoperative blood loss volume and inhospital stay duration were lower in the TLH than in the TAH group. [ 1 3 5 6 7 8 9 10 11 12 13 14 15 ] In our study, blood loss volume was lower in the TLH group than in the TAH group by an average of 150 mL, possibly due to blood loss during skin incision and the use of traditional hemostasis (clamping and tying) compared to advanced bipolar energy used in TLH. Similarly, other studies have related this effect to the magnified visual field and the use of bipolar diathermy.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In current study patient satisfaction was found highly significant between TLH and TAH (100% versus 56%, p<0.001) similar result was showed by Gupta et al 23 The reason for better postoperative comfort in TLH was that it required only a small skin incision, thereby resulting in reduced postoperative pain and minimal blood loss. Consequently, patients can quickly resume the activities of daily living and TLH could contribute to patients' quality of life as also observed by Komatsu et al 30 Postoperative follow up of patients 4 weeks after discharge showed better quality of life, lesser morbidity and higher satisfaction rate in TLH group.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were reported by Gupta et al in their comparative study between TLH and conventional TAH in non-neoplastic uterine diseases. 23 In present study the comparison regarding postoperative day of catheter removal was significant between TLH and TAH groups (2.00±0.00 versus 3.96±2.92; p=0.002). In TLH group catheter was removed on second postoperative day in all patients, but in TAH group in 88% ( 22) of patient's catheter were removed on third day, but in 4% (1) patient on 5th day and in 4% (1) patient in 7th day because bladder adherent to lower uterine segment and in 4% (1) patient on 21st day because there was bladder injury happened.…”
Section: Discussionmentioning
confidence: 44%